From Feed to Field: Digital Promotion and Communication in Local Tennis Communities - Muhammad Firrizqi Alchoiri; Bambang S. Wijaya (Jobmark: Journal of Branding and Marketing Communication, 2023)
This study investigates the transformative role of digital ecosystems in mobilizing local sports communities, focusing on the "Tennis Bae Bekasi" collective. By analyzing the strategic synergy between Instagram and the Kuyy app, the research explores how digital promotion facilitates audience engagement and membership growth in the post-digital era. Utilizing a qualitative case study approach supported by questionnaires and systematic observations, the study decodes the mechanisms through which high-fidelity visual storytelling (comprising high-quality video content and curated photography) converts digital "feeds" into active "field" participation. The findings demonstrate that integrated digital strategies significantly amplify community reach and foster sustained engagement by bridging the gap between virtual interaction and physical sporting activities. The results offer critical insights into the optimization of niche sports communication, suggesting that interactive content and collaborative digital frameworks are essential for community longevity. This research contributes to the field of digital sports marketing by highlighting the shift from passive viewership to active community involvement within localized tennis networks.